Drynaria fortunei improves lipid profiles of elderly patients with postmenopausal osteoporosis via regulation of Notch1-NLRP3 inflammasome-mediated inflammation. (1st February 2022) - Lu, Lin; Wang, Zhi; Zhang, Hanqing; Liu, Tongou; Fang, Hong
Abstract: Background: Dyslipidemia is a common comorbidity in elderly patients with postmenopausal osteoporosis (PMOP). Drynaria fortunei (Rhizoma drynariae) is well-known in traditional Chinese medicine for its ability to improve bone mineral density (BMD). However, whether and how Drynaria fortunei improves plasma lipid profiles in elderly PMOP patients remains unclear. Methods: Eighty elderly female patients with concurrent PMOP and hyperlipemia were randomly assigned to Drynaria fortunei 2( n = 40) or control ( n = 40) groups. The clinical efficacies of Drynaria fortunei were evaluated. At 0, 3-, 6-, 9-, and 12-month of follow-up, plasma levels of IL-1β, IL-18, TNF-α, IL-6, IL-8, and IL-10 were measured using ELISA, whereas PBMC levels of NLRP3, ASC, caspase-1, NF-κB, SIRT1, and Notch1 were measured using RT-qPCR. PBMC isolated from PMOP patients were cultured and treated with Drynaria fortunei to determine its influence on NLRP3 inflammasome and associated cytokines. Results: Drynaria fortunei effectively improved patients' BMD and lipid profiles. IL-1β, IL-18, TNF-α, IL-6, IL-8 levels, as well as inflammasome-molecules of NLRP3, ASC, caspase-1, and NF-κB increased over time in the control group, but were significantly attenuated with Drynaria fortunei administration. In vitro, Drynaria fortunei suppressed NLRP3 inflammasome and associated cytokines by increasing SIRT1 or decreasing Notch1. Drynaria fortunei had inhibitory effects on NLRP3 inflammasome and Notch1 even when SIRT1 expression was suppressed. Conclusions: Drynaria fortunei has been demonstrated to significantly improve lipid profiles for elderly PMOP patients. Drynaria fortunei may down-regulate Notch1 independently of SIRT1 to suppress NLRP3 inflammasome-mediated inflammation, thus improving plasma lipid profile.